2006
DOI: 10.1007/s11430-006-0839-x
|View full text |Cite
|
Sign up to set email alerts
|

Southeastern extension of the Red River fault zone (RRFZ) and its tectonic evolution significance in western South China Sea

Abstract: Recent geophysical surveys and basin modeling suggest that the No.1 fault in the Yinggehai basin (YGHB) is the seaward elongation of the Red River fault zone (RRFZ) in the South China Sea (SCS). The RRFZ, which separates the South China and Indochina block, extends first along the Yuedong fault, offshore of Vietnam, and then continues southward and breaks off into two branches: the Lupar fault and the Tinjia fault. The southern extension of the Lupar fault dies out beneath the NW Borneo while the Tinjia fault … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…This phenomenon is likely related to the metamorphic rock belt, with a length of ∼900 km and a width of ∼10∼20 km, formed along the Xuelong Mountain, the Diancang Mountain and the Ailao Mountain near the Red River fault and along the Day Nui Con Voi Mountain in Vietnam (Xu et al, 2003). Previous researchers' results have shown that the Red River fault zone is the divider between the Eurasian and Indian plates, and its eastern side extends into the South China Sea Liu et al, 2006). The characteristic that the magnetic anomalies are relatively weak in the area on the west of the Lijiang-Xiaojinhe fault and the Red River fault and relatively strong in the area on the east supports the speculation that the Tibetan Plateau and Yangtze blocks are divided by these two fault zones (Zhong et al, 2005).…”
Section: Magnetic Anomalies and Geological Structurementioning
confidence: 86%
“…This phenomenon is likely related to the metamorphic rock belt, with a length of ∼900 km and a width of ∼10∼20 km, formed along the Xuelong Mountain, the Diancang Mountain and the Ailao Mountain near the Red River fault and along the Day Nui Con Voi Mountain in Vietnam (Xu et al, 2003). Previous researchers' results have shown that the Red River fault zone is the divider between the Eurasian and Indian plates, and its eastern side extends into the South China Sea Liu et al, 2006). The characteristic that the magnetic anomalies are relatively weak in the area on the west of the Lijiang-Xiaojinhe fault and the Red River fault and relatively strong in the area on the east supports the speculation that the Tibetan Plateau and Yangtze blocks are divided by these two fault zones (Zhong et al, 2005).…”
Section: Magnetic Anomalies and Geological Structurementioning
confidence: 86%
“…The collision between the Indian plate and Eurasian plate led to the extrusion of Indo-China and formed a seires of strike-slip faults and basins (eg, Yinggehai Basin, Zhongjiannan Basin, Wanan basin). However, other scientists have argued that the basins in the western South China Sea don't match the escape structure model (Liu et al 2004;Liu et al 2006;Clift et al 2008;Zhu et al 2009). Therefore, the mechanism of the Wan-An Basin need to be redefined.…”
Section: Discussion Previous Studies On the Basin Type Of Wan-an Basinmentioning
confidence: 99%
“…The center of Yao, 1996;Wu et al 2006;Liu et al 2006) the basin is thicker than the edge. The depocenter moved eastward significantly, and developed shallow -bathyal facies.…”
Section: Pliocene -Quaternarymentioning
confidence: 97%
“…This section focused on the effects of tectonic activity of the RRF on the sedimentary process at about 5.7 Ma. As the boundary of the Eurasian plate and the Indo-Australian plate, the evolution of the RRF showed direct relationships with the uplift of the Tibet Plateau and the expansion of the South China Sea (Liu et al, 2006). Previous studies proposed that the RRF shifted sinistrally during 11.6-5.7 Ma caused by the wedging of the Indian plate into the Eurasian plate and the extrusion of South China Block, whereas, with the further SE movement of the South China Block, from 5.7 Ma to present, the RRF shifted from sinistral to dextral (Allen et al, 1984;Rangin et al, 1995).…”
Section: Tectonic Activity Of the Rrf At About 57 Mamentioning
confidence: 97%